A composite index for predicting improvement of mitral regurgitation in patients with multivalvular heart disease after transcatheter aortic valve replacement - Xiao, Zhi-Cheng; Zheng, Gui-Bin; Geng, Tian-Xiang; Lu, Zhong-Fei; Wang, Zhen; Zheng, Lei; Ren, Meng-Meng; Ren, Fa-Xin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTranscatheter aortic valve replacement (TAVR) has become a standard treatment for severe aortic stenosis (AS). Concomitant mitral regurgitation (MR) is observed in approximately 19%–29% of these patients. Although MR frequently improves after TAVR, persistent MR is associated with worse clinical outcomes, highlighting the need for reliable predictors of MR persistence.MethodsWe conducted a single-center, retrospective study that included 53 patients with severe AS and moderate-to-severe MR who underwent TAVR between 2017 and 2024. The primary outcome was MR improvement, defined as a reduction of at least one grade at the 1-year follow-up. To identify independent predictors, we performed multivariable logistic regression analysis.ResultsAt 1-year follow-up, MR improvement was observed in 67.9% of patients. Multivariable analysis identified persistent atrial fibrillation [odds ratio (OR): 0.099, 95% CI: 0.017–0.575; P = 0.01] and eccentric MR (OR: 0.066, 95% CI: 0.012–0.370; P = 0.002) as independent negative predictors of improvement. Conversely, greater interventricular septal thickness (OR: 1.825, 95% CI: 1.075–3.099; P = 0.026) was a positive predictor. A composite predictive index integrating these three variables demonstrated excellent discriminative ability, with an area under the receiver operating characteristic curve of 0.909.ConclusionThis study identifies persistent atrial fibrillation, eccentric MR, and interventricular septal thickness as key independent predictors of MR improvement after TAVR. The derived composite index, with its outstanding predictive performance, provides a novel tool to aid in patient selection and prognostic assessment.